Cell-envelope remodeling as a determinant of phenotypic antibacterial tolerance in mycobacterium tuberculosis - Larrouy-Maumus, Gérald; Marino, Leonardo B. [UNESP]; Madduri, Ashoka V. R.; Ragan, T. J.; Hunt, Debbie M.; Bassano, Lucrezia; Gutierrez, Maximiliano G.; Moody, D. Branch; Pavan, Fernando R. [UNESP]; De Carvalho, Luiz Pedro S. (American Chemical Society (ACS), 2016)
The mechanisms that lead to phenotypic antibacterial tolerance in bacteria remain poorly understood. We investigate whether changes in NaCl concentration toward physiologically higher values affect antibacterial efficacy against Mycobacterium tuberculosis (Mtb), the causal agent of human tuberculosis. Indeed, multiclass phenotypic antibacterial tolerance is observed during Mtb growth in physiologic saline. This includes changes in sensitivity to ethionamide, ethambutol, d-cycloserine, several aminoglycosides, and quinolones. By employing organism-wide metabolomic and lipidomic approaches combined with phenotypic tests, we identified a time-dependent biphasic adaptive response after exposure of Mtb to physiological levels of NaCl. A first rapid, extensive, and reversible phase was associated with changes in core and amino acid metabolism. In a second phase, Mtb responded with a substantial remodelling of plasma membrane and outer lipid membrane composition. We demonstrate that phenotypic tolerance at physiological concentrations of NaCl is the result of changes in plasma and outer membrane lipid remodeling and not changes in core metabolism. Altogether, these results indicate that physiologic saline-induced antibacterial tolerance is kinetically coupled to cell envelope changes and demonstrate that metabolic changes and growth arrest are not the cause of phenotypic tolerance observed in Mtb exposed to physiologic concentrations of NaCl. Importantly, this work uncovers a role for bacterial cell envelope remodeling in antibacterial tolerance, alongside well-documented allterations in respiration, metabolism, and growth rate.
Keywords: cell envelope remodeling; lipids; Mycobacterium tuberculosis; osmolarity; phenotypic antibacterial tolerance